From textbooks to cheque books: Charting financial literacy paths for university students - Zaiton Osman; Ing Grace Phang; Izyanti Awg Razli (Universiti Malaysia Sabah, 2024)
Being financially literate is fundamentally essential, especially for university students who are on the cusp of transitioning into the workforce and facing the challenge of independently managing their finances. This skill is particularly critical as they prepare to make significant financial decisions, navigate through various financial responsibilities, and establish a foundation for their future economic well-being. The primary objective of this study is to assess financial literacy among university students and explore variations based on gender, age, and academic programs. The study involved the participation of 299 university students, and data collection occurred both at the onset and culmination of the semester. The study's findings reveal that there exists no noteworthy gender-based disparity in terms of financial literacy. Nevertheless, notable distinctions emerged in the domain of basic financial literacy questions when analysed across different age groups, as well as in advanced financial literacy questions when scrutinized by the program of study. These findings bear relevance for educators and policymakers, as they suggest the necessity for tailored interventions aimed at augmenting financial literacy among university students. Furthermore, this study serves as a compass guiding future research endeavours in the realm of financial literacy.